Land Tipology and Mangrove Vegetation Condition of Bulaksetra, Pangandaran District, West Java Province TIPOLOGI DAN KONDISI VEGETASI KAWASAN MANGROVE BULAKSETRA KABUPATEN PANGANDARAN PROVINSI JAWA BARAT - Cecep Kusmana; Dewi Rahayu Purwa Ningrum (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Mangrove forests in Indonesia has been declining and need rehabilitation efforts. The rehabilitation it self needs actual data af the site. Bulaksetra mangrove was destroyed because of tsunami disaster. Based on that condition the purpose of this research was to consider the typology of area and to explore the condition of mangrove vegetation at Bulaksetra, Pangandaran, West Java. Variabel to be measured in this research were stem diameter, tree hight, number of individual, and depth of inundiation. Data colection method was carried on using a combination of between strip method for trees inventory and strip square method for regeneration, totaled 34 unit transects. The depth of inundation performed at 27 sampled points spread at all research areas. Our result obtained showed that, mangrove vegetation at Bulaksetra consists of three classes of crown density: high mangrove density, medium mangrove density, and low mangrove density lead at 3 tipology catagories (A1 : high water inundation <2 cm area; A2: high water inundation 2–5 cm; A3: high water inundation > 5 cm). In this moment Bulaksetra area is covered by 19 mangrove species, in which 8 species are true mangroves. A1 and A3 land tipologyes dominated by Avicennia alba, meanwhile A2 land tipology dominanted by Nypa fruticans.Generally mangrove vegetations in Bulaksetra does not from a zonation but growing mixed in this area.Key words: Bulaksetra, mangrove, typology, water inundation, zonation.